2022
DOI: 10.3389/fpubh.2022.808763
|View full text |Cite
|
Sign up to set email alerts
|

A Micro-Level Analysis of Physiological Responses to COVID-19: Continuous Monitoring of Pregnant Women in California

Abstract: Continuous monitoring of perinatal women in a descriptive case study allowed us the opportunity to examine the time during which the COVID-19 infection led to physiological changes in two low-income pregnant women. An important component of this study was the use of a wearable sensor device, the Oura ring, to monitor and record vital physiological parameters during sleep. Two women in their second and third trimesters, respectively, were selected based on a positive COVID-19 diagnosis. Both women were tested u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Twenty-one studies described the application of wearable sensors to collect information about maternal parameters and activities during pregnancy [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These studies are described in Table 2 , together with a summary of the design and population, wearable device used, and main findings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-one studies described the application of wearable sensors to collect information about maternal parameters and activities during pregnancy [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These studies are described in Table 2 , together with a summary of the design and population, wearable device used, and main findings.…”
Section: Resultsmentioning
confidence: 99%
“…In their first study, Jimah and colleagues reported significant correlations between objective and self-reported measures by analysing a pregnant woman at 33 weeks of gestation [ 31 ]. In a later study, these authors also reported physiological changes in resting heart rate and variability, respiratory, and sleep in two pregnant women after the onset of COVID-19 symptoms [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the initial screening, the full texts of the remaining 43 documents were reviewed. Three opinion articles [23][24][25], four review articles [6,[26][27][28], two case reports or case series [29,30], one long COVID study [31], five studies that did not report HRV [32][33][34][35][36], eleven studies without a control group [37][38][39][40][41][42][43][44][45][46][47], and one study that used data from the journal article which was the same as the data presented in the conference abstract [48] were excluded. The inter-rater agreement rate among the researchers in the full texts review was 97.67% (42/43).…”
Section: Study Selectionmentioning
confidence: 99%